Prevalence of depressive symptoms among the clients maintained in methadone maintenance treatment programme at Tribhuvan University Teaching Hospital - Pathak, N.; Ojha, S.P.; Sharma, V.D. (Journal of Psychiatrists’ Association of Nepal, 2017)
Introduction: Depression is widely prevalent among the former opioid addicts in Methadone Maintenance Treatment (MMT). It is important to be aware of its severity as it plays a crucial role in methadone dosage, length of time in treatment and the relapse rate. The co-existence of depression is seen to worsen the prognosis in outcome of MMT. Objective: This study aimed to study the prevalence of the symptoms of depression among MMT clients. Method: This is a descriptive and Cross-Sectional study done in 60 MMT clients attending the out patients clinic in Tribhuwan University Teaching Hospital, Nepal. A structured proforma was constructed obtaining the data regarding age, sex, religion, occupation, marital status, literacy rate and socio-economical status. Depressive symptoms were evaluated using 21-item BDI scale. Result: Depressive symptoms were found in 63.3 % of the patients. 38.3% had mild to moderate depression, 15% had moderate to severe, and 11.7% had severe level of depressive symptoms. The depressive symptoms were most prevalent among females (90%) and age group 40-50 years. The prevalence of depressive symptoms were more in unmarried (82%), unemployed (65%), lower socio-economic class(71%) and completing only secondary level in education (73%). Conclusion: The major risk factors for depression among former opioid users were female gender, unmarried, low education level, unemployment and low socio-economic status.